Extended chronology of the Cordón Caulle volcanic eruption beyond 2011 reveals toxic impacts - Fluck, Werner Thomas (2016)
Aside of immediate impacts, the 2011 Puyehue–Cordón Caulle volcano (PCC) eruption also caused persisting chemical impacts. By 2012, toxicity resulted in overt dental fluorosis in deer, with bone fluoride increasing > 38-fold to 5175 ppm. Sheep, horses and cattle also succumbed to fluorosis. Due to eolian redeposition of tephra, exposure of ruminants continued, bone fluoride reached 10 396 ppm, and by 2014 skeletal fluorosis was found. Nonskeletal fluorosis resulted in reduced wool growth and major losses among periparturient cattle. Peculiarities of digestive processes make ruminants susceptible to fluoride-containing tephra, which averaged 548 ppm from PCC. Moreover, recent volcanic eruptions causing fluorosis could be aggravated by local iodine deficiency, which increases the incidence and harshness of fluorosis, and deficiency of selenium, which, among other things, also results in secondary deficiency of iodine. Notwithstanding, several measures are available to livestock producers to minimize chemical impacts of fluoride.